Phylogenetic study of the genus Aptychella (Pylaisiadelphaceae, Musci) - Hiroyuki Akiyama (2018)
Copyright © 2015 by The American Bryological and Lichenological Society, Inc. The relationships among species of the epiphytic genus Aptychella (Broth.) Herzog and Clastobryopsis M. Fleisch. were inferred based on phylogenetic analyses of plastid (rpl16, rps4, and trnL-F) and mitochondrial (nad5) gene sequences as well as morphological features. One of the Asian members, Aptychella robusta (M. Fleisch.) M. Fleisch., exhibits much genetic variation and differentiation among populations, which may reflect the presence of cryptic species. The distinctiveness of Asian members characterized by unicostate leaves, A. brevinervis (M. Fleisch.) M. Fleisch., A. pseudobrevinervis H. Akiyama and A. oblongifolia H. Akiyama, are confirmed. On the contrary, Aptychella proligera, the sole member of the genus known from South and Central America, is shown to have a close relationship to the A. brevinervis complex and preserves low genetic variation among samples collected from geographically remote localities. This lack of variation might be caused by a recent immigration from Asian populations. The Asiatic genus Clastobryopsis is treated as a synonym of Aptychella based on the present phylogenetic analyses. One new combination is proposed-Aptychella imbricata (H. Akiyama et al.) H. Akiyama comb. nov.